Cover Picture: Screening and interlayer coupling in multilayer MoS2 (Phys. Status Solidi RRL 5/2013). Issue 5 (15th May 2013) - Naumann, Volker; Lausch, Dominik; Graff, Andreas; Werner, Martina; Swatek, Sina; Bauer, Jan; Hähnel, Angelika; Breitenstein, Otwin; Großer, Stephan; Bagdahn, Jörg; Hagendorf, Christian
<x xml:space="preserve">Abstract</x> Potential‐induced degradation (PID) of photovoltaic solar modules gained a lot of interest during the last three years. Many PID‐affected modules based on crystalline silicon show intense shunting of the solar cells. In the past, character and origin of these PID‐shunts have not been clear. In the contribution by Naumann et al. (see pp. 315–318) monocrystalline and multicrystalline silicon solar cells have been prepared with PID of the shunting type. In plan view, SEM using electron beam induced current and secondary ion mass spectrometry measurements reveal local PID‐shunts correlated with sodium accumulations. Detailed TEM investigations at cross sections of PID‐shunts reveal stacking faults in silicon decorated with sodium. It is concluded that the sodium decorated stacking faults provide paths with high conductivity across the p–n junction, thus leading to the observed shunting. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>